2016
DOI: 10.1038/srep35569
|View full text |Cite
|
Sign up to set email alerts
|

DCE-MRI Perfusion and Permeability Parameters as predictors of tumor response to CCRT in Patients with locally advanced NSCLC

Abstract: In this prospective study, 36 patients with stage III non-small cell lung cancers (NSCLC), who underwent dynamic contrast-enhanced MRI (DCE-MRI) before concurrent chemo-radiotherapy (CCRT) were enrolled. Pharmacokinetic analysis was carried out after non-rigid motion registration. The perfusion parameters [including Blood Flow (BF), Blood Volume (BV), Mean Transit Time (MTT)] and permeability parameters [including endothelial transfer constant (Ktrans), reflux rate (Kep), fractional extravascular extracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 44 publications
4
39
2
1
Order By: Relevance
“…Although brain tumors are different from other tumors due to their unique BBB structure, previous studies of malignant tumors outside the brain, such as cervical cancer, colorectal cancer, and lung cancer, have demonstrated that increased permeability or angiogenesis was related to a favorable tumor response. [11][12][13] Therefore, there is a possibility that increased permeability at certain time points might be related to a favorable treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Although brain tumors are different from other tumors due to their unique BBB structure, previous studies of malignant tumors outside the brain, such as cervical cancer, colorectal cancer, and lung cancer, have demonstrated that increased permeability or angiogenesis was related to a favorable tumor response. [11][12][13] Therefore, there is a possibility that increased permeability at certain time points might be related to a favorable treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in these underlying parameters occur early in the progression of malignant disease, making ν ec and K trans useful as potential biomarkers and for assessing drug or oxygen delivery. Both K trans and ν ec have been clinically used as predictive markers of disease and treatment response, demonstrating their relevance in prognosis and treatment evaluation [2][3][4]30].Limited work has been done with microscopy to perform tissue compartment modeling to identify vascular permeability [12,22]. Moreover, to our knowledge there have been no successful attempts to fit time-lapsed microscopy data of local plasma and tissue concentrations to perform compartment modeling and obtain K trans and ν ec for the local vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…The application of automatically extracted personalized AIFs is limited because of various factors, such as motion artifacts and temporal resolutions. 21 Therefore, we used a manual selection of individual AIFs with an ROI placed on internal iliac artery on transverse plane at the peak arterial enhancement phase. Second, Tofts mode was selected to calculate the perfusion parameters because that this model gave good fits to data and the signal-tonoise ratio was sufficiently high that parametric images were not influenced significantly by noise.…”
Section: Discussionmentioning
confidence: 99%